PROMOSI INDUSTRI BATIK PEKALONGAN (Penerapan, Kemudahan, dan Hambatan) - Tamamudin (Jurnal Hukum Islam, 2015)
Pekalongan city is one of the produce regions batik. Geographically, small industry and large garment industry compete in the marketing of Pekalongan batik spread and extends beyond Pekalongan. Promotion strategy itself is the best combination of variables advertising, personall selling, promotions and other publicity semuanaya planned to achieve sales program. The type of research is a field research. The approach used in the study is a qualitative approach, the research procedures that produce descriptive data, in the form of words written or spoken of the people and observed behavior. Batik industry in Pekalongan in the implementation of the strategy promotion strategy promotional mix or promotional mix (promotional mix) that is noticed and keep the blend of Personal selling by opening stores or shop and email services for e-commerce, advertising to advertise in several electronic media and newspapers, sales promotion with several exhibitions held in Pekalongan Pekalongan and outside the city, and publicity by utilizing the internet.